REVIEW ON THE MIRACLE ROLE OF CHIA SEEDS (SALVIA HISPANICA L.) NUTRITIONAL AND BIOACTIVE COMPOUNDS IN THE TREATMENT OF CARDIOVASCULAR DISORDER - Tamsheel Fatima Roohi (Journal of Biomedical and Pharmaceutical Research, 2020)
Chia (Salvia hispanica L.) have growing research interest globally which determined it as functional food which acts as biochemical targets for the treatment of various cardiovascular disorder with reduced toxicological value. It is worldwide popular because of its nutritional, bioactive, and phytochemical compounds value, used as an ingredient in many food industries due to its high dietary fibre content value. Their consumption rate is higher in past years due to the presence of omega-3 fatty acids, proteins, amino acids (essential), and a good source of bioactive peptides. Many researchers focussed on α-linolenic acid which is the effective pioneer of maintenance of functioning of polyunsaturated fatty acids (PUFAs). Chia seed oil is investigated on different screening models either clinically or pre-clinically and demonstrate the levels of the serum lipid profile, diabetic severity changes. The review of the literature highlights the miracle values of the different nutritional composition, antioxidant values, phytochemical constituents, and the role of these in treatment of various cardiovascular disorder such as hypertension, inflammation, atherosclerosis, diabetes. The review highlights antioxidants values, which change the enzyme activities of the liver, blood. There is need to more focussed on the mechanistic approaches on the pharmacological aspects of the chia seeds with respective biological compounds in either clinical trial and animal screening trial before applied to it as a functional food for the therapeutic action in the treatment of diseases.Keywords: Salvia hispanica L. (Chia), Antioxidants, Biological properties of Salvia hispanica L. (Chia).